A escritura musical nos ambientes da eletrônica em tempo real - Kafejian, Sergio [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The objective of this research is to understand how the processes of musical writing are built in compositional projects involving live electronics. For this purpose, it was necessary to question the concept of musical writing; to examine the historical and technical conditions that gave rise to musical writing; and to investigate how the processes of musical writing are established and how they relate to the processes of creation and perception of instrumental and electroacoustic music. After investigating the theoretical production of twentieth‐century composers who dedicated themselves to conceptualize musical writing – specially Pierre Boulez, Philippe Manoury, Hughes Dufourt and Flo Menezes –, an artistic research was undertaken involving two compositions for acoustic instruments and live electronics. These two compositions, extensively documented in this work, demonstrate how the processes of musical writing are established during the various stages of musical composition

O objetivo desta pesquisa é compreender como os processos de escritura musical se instituem nos projetos composicionais envolvendo os recursos de eletrônica em tempo real. Para tal, fez se necessário compreender o que vem a ser a escritura musical; examinar as condições históricas e técnicas que possibilitaram o desenvolvimento da escritura musical; e investigar como os processos de escritura se instituem e se relacionam com os processos de criação e de percepção musicais, sejam eles instrumentais ou eletroacústicos. Em um segundo momento, após termos investigado a produção teórica de compositores do século XX que se dedicaram a conceituar a escritura musical – especificamente Pierre Boulez, Philippe Manoury, Hughes Dufourt e Flo Menezes –, empreendeu‐se uma pesquisa de criação musical envolvendo instrumentos acústicos e eletrônica em tempo real. Nesta pesquisa de criação, extensamente documentada neste trabalho, procuramos demonstrar como os processos de escritura se estabelecem no decorrer das diversas etapas da composição musical
Keywords: Composição (Musica); Música - Séc. XX; Musica eletronica; Electronic music